Optimalisasi Pemasaran UMKM melalui Branding dan Media Digital pada UMKM di Kelurahan Pasuluhan, Kecamatan Walantaka, Kota Serang, Banten - Lelis Reminis There; Sabila Sofyana Zahra; M. Irfan Andrianto; Raihan Raihan; Sonata Mahardika; Desta Adji Saputra; Raihan Ahmad Musyaffa; Muhammad Rifki Arrosyid; Ardian Sah; Siswo Wardoyo (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to improve the digital understanding and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Pasuluhan Village, Walantaka District, Serang City, Banten. The main problems faced by these MSME actors include a weak product visual identity (branding), conventional packaging, limited market reach that relies on word-of-mouth methods and traditional market sales, and a lack of digital technology understanding. The implementation method used is a participatory approach and direct mentoring guided by the service team (Participatory Action Research), which of three stages: observation, material preparation, and workshop execution. The results of this activity show an increase in participants' skills, evidenced by the creation of business Gmail accounts, the visualization of logo design variations for the 9 attending MSMEs using Artificial Intelligence (ChatGPT) technology, improvements in packaging aesthetics, and the creation of marketplace accounts on the Shopee and TikTok Shop platforms. This program received a highly positive response from village officials and local cadres as it has proven to provide concrete solutions for expanding market access for Pasuluhan's local crafts and culinary products online.